Fast Prediction for Criminal Suspects through Neighbor Mutual Information-Based Latent Network - Jhee, Jong Ho; Kim, Myung Jun; Park, Myeonggeon; Yeon, Jeongheun; Shin, Hyunjung (International Journal of Intelligent Systems, 2023)
One of the interesting characteristics of crime data is that criminal cases are often interrelated. Criminal acts may be similar, and similar incidents may occur consecutively by the same offender or by the same criminal group. Among many machine learning algorithms, network-based approaches are well-suited to reflect these associative characteristics. Applying machine learning to criminal networks composed of cases and their associates can predict potential suspects. This narrows the scope of an investigation, saving time and cost. However, inference from criminal networks is not straightforward as it requires being able to process complex information entangled with case-to-case, person-to-person, and case-to-person connections. Besides, being useful at a crime scene requires urgency. However, predictions from network-based machine learning algorithms are generally slow when the data is large and complex in structure. These limitations are an immediate barrier to any practical use of the criminal network geared by machine learning. In this study, we propose a criminal network-based suspect prediction framework. The network we designed has a unique structure, such as a sandwich panel, in which one side is a network of crime cases and the other side is a network of people such as victims, criminals, and witnesses. The two networks are connected by relationships between the case and the persons involved in the case. The proposed method is then further developed into a fast inference algorithm for large-scale criminal networks. Experiments on benchmark data showed that the fast inference algorithm significantly reduced execution time while still being competitive in performance comparisons of the original algorithm and other existing approaches. Based on actual crime data provided by the Korean National Police, several examples of how the proposed method is applied are shown.
Keywords: Crime data; Criminal acts; Criminal case; Criminal networks; Fast inference; Inference algorithm; Machine learning algorithms; Machine-learning; Mutual informations; Network-based